Molecular basis of rare congenital bleeding disorders. (May 2023) - Dorgalaleh, Akbar; Bahraini, Mehran; Shams, Mahmood; Parhizkari, Fereshteh; Dabbagh, Ali; Naderi, Tohid; Fallah, Aysan; Fazeli, Alieh; Ahmadi, Seyed Esmaeil; Samii, Amir; Daneshi, Maryam; Heydari, Farshad; et al.
Abstract: Rare bleeding disorders (RBDs), including factor (F) I, FII, FV, FVII, combined FV and FVIII (CF5F8), FXI, FXIII and vitamin-K dependent coagulation factors (VKCF) deficiencies, are a heterogeneous group of hemorrhagic disorder with a variable bleeding tendency. RBDs are due to mutation in underlying coagulation factors genes, except for CF5F8 and VKCF deficiencies. FVII deficiency is the most common RBD with >330 variants in the F7 gene, while only 63 variants have been identified in the F2 gene. Most detected variants in the affected genes are missense (>50% of all RBDs), while large deletions are the rarest, having been reported in FVII, FX, FXI and FXIII deficiencies. Most were located in the catalytic and activated domains of FXI, FX, FXIII and prothrombin deficiencies. Understanding the proper molecular basis of RBDs not only can help achieve a timely and cost-effective diagnosis, but also can help to phenotype properties of the disorders.